Explicating Politicians' Arguments for Sex Quotas in Sweden: Increasing Power and Influence Rather Than Increasing Quality and Productivity - Madison, Guy (Frontiers in Communication, 2019)
Quotas are employed or proposed in several European countries as a means to decrease differences in outcomes across groups. Quotas belong to a family of biased selection and treatment measures based on group membership, rather than individual ability. The effects of such measures depend on the underlying model of the relevant variables and their relationships, but this model is not explicit in the political discourse. Here, thematic analysis is applied to statements that argue for legislated sex quotas in Sweden, issued by leading politicians and government officials. The most common, recurrent themes are that: (a) Women are at least as able as men; (b) less able men are currently selected over more able women; (c) the proportion of women should be increased to at least 40%, which (d) will increase organizations' quality and productivity; (e) this should be achieved by means of quotas but (f) not through improved meritocratic assessment. It is shown that these claims are inconsistent, as (1) improved meritocratic assessment was not proposed, although that would more effectively select the more able than would quotas, and (2) quotas will lead to lower rather than higher quality and productivity, as it demands that the less able be appointed if they are female. This suggests that the purpose of quotas is to increase the influence of the favored group even if it is currently less able.